(untitled) (Experimental biology, 2018)
Ecology and stress are the most important causes of hormonal disorders of human. The reproductive system is the most sensitive system of the women, it can react to small changes in the external and internal environment. Nowadays, 15% of couples have infertility, the cause of which are endocrine disorders and hormonal disbalance. According to this, the research of the functional activity of the reproductive system of women is the actual problem, which needs serious approach. The mission of this work is research the concentration of gonadotropic hormones (FSH and LH) in blood of women in Almaty, comparing them with the normal, research of connecting between hormonal disorders and ecology and stress. To find the causes of hormonal disorders, we have researched the hormone cortisol – the main stress hormone, which suppresses the secretion of hormones secreted by the hypothalamus, pituitary gland, ovaries and responsible for the regulation of the female reproductive system. The research was based on the City Human Reproduction Center. The level of LH, FSH and cortisol in the blood was studied in 130 women of reproductive age from 20 to 30 years. The concentration of hormones was determined by the method of enzyme immunoassay. The medium results of normal level are LH 4,64 ± 0,26 IU/l, FSH 7,28 ± 0,27 IU/l, LH/FSH 1,12 ± 0,04, cortisol 367,32 ± 15,006 nmol/l. Hight concentration for LH is 24,37 ± 2,54 IU/l, FSH is 31,69 ± 6,006 IU/l, LH/FSH is 2,15 ± 0,19, cortisol is 2,15 ± 0,19 nmol/l. The average results of reduced concentration are LH 0,35 ± 0,05 IU/l, FSH 1,26 ± 0,27 IU/l, LH/FSH 0,44 ± 0,02, cortisol 110,76 ± 11,07 nmol/l. The revealed deviations in the level of hormones are probably associated with a change in the level of cortisol and the negative influence of environmental factors. Key words: reproductive system, luteinizing hormone (LH), Follicle-stimulating hormone (FSH), cortisol.